Solutions for online access to copyright works belonging to the collections of documentary and cultural heritages institutions - Ramos Simón, Luis Fernando; Blázquez Ochando, Manuel (Revista General de Información y Documentación, 2018)
This article analyses the possible legal solutions for digitalisation of protected works deposited in documentary and cultural heritage institutions. The main difficulty in achieving this objective is the requirement that protected works cannot be used - before they enter the public domain - without the agreement between the owners of the rights of those works and the users. Two main ways to access the works are studied. The first is agreements between owners and cultural institutions, where some applied schemes and experiences are explored, the most promising being the path of collective agreements, which seems to safeguard the interests of holders through a system of guarantees. The other way is the application of exceptions and limits in application of European Union legislation, several exceptions are studied, such as the one referring to orphan works and out-of-commerce-works and the on-site consultation. This way of exceptions and limits of rights is insufficient due to the complexity to regulate access to the works, as well as insecurity and high management costs to obtain the consent of the owners. There is also a need to adopt some of the legal solutions that avoid legal gaps and generate a safe environment for cultural, scientific and intellectual exploitation
Keywords: Digitization; Copyright; Online; Digital heritage; Cultural institutions; Reuse of public sector information; Licenses; Out of commerce works; Orphan works